2002
DOI: 10.1164/rccm.2109061
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related Differences in Cough Reflex Sensitivity in Patients with Chronic Cough

Abstract: Among patients attending specialist cough clinics there is an excess of females, but the reason for this sex difference is unknown. We tested the hypothesis that the sensitivity of the cough reflex is greater in female compared with male patients with chronic cough. Inhalation cough challenges with capsaicin and citric acid were performed in a large group of patients with chronic cough. The concentrations of tussive agent causing two (C2) and five (C5) coughs were calculated. Measurements of capsaicin cough re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
87
3
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(112 citation statements)
references
References 26 publications
9
87
3
9
Order By: Relevance
“…Females have a heightened sensitivity of the cough reflex as revealed by inhalational challenge with citric acid [17,18], tartaric acid [19], and capsaicin [20]. This increased sensitivity of the cough reflex is also demonstrable in patients attending the cough clinic [21] where objectively recorded cough in females is twice that of males [18]. Together these observations would suggest that females have an increased sensitivity of the cough reflex in comparison with males.…”
Section: Discussionmentioning
confidence: 93%
“…Females have a heightened sensitivity of the cough reflex as revealed by inhalational challenge with citric acid [17,18], tartaric acid [19], and capsaicin [20]. This increased sensitivity of the cough reflex is also demonstrable in patients attending the cough clinic [21] where objectively recorded cough in females is twice that of males [18]. Together these observations would suggest that females have an increased sensitivity of the cough reflex in comparison with males.…”
Section: Discussionmentioning
confidence: 93%
“…Fontana). debate (Widdicombe, 2001). Animal experiments performed in vivo have revealed that RARs and C-fibre sensory receptors may be activated by both non-isotonic water solutions and capsaicin, albeit to different extents (Pisarri et al, 1991(Pisarri et al, , 1992Mohammed et al, 1993;Morikawa et al, 1997), and many inhalation studies have confirmed the powerful tussigenic action of these agents in normal subjects and in patients with respiratory and nonrespiratory disorders (Higenbottam et al, 1989;Fontana et al, 1997Fontana et al, , 1998Fontana et al, , 1999aDavenport et al, 2002;Kastelik et al, 2002;Dicpinigaitis, 2004). A peculiar type of low-threshold mechanoreceptors innervated by myelinated vagal fibres has been described recently in the guinea pig extrapulmonary airways (Canning et al, 2004;Mazzone, 2005;Mazzone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy women have a more sensitive cough reflex than do healthy men [8,9], and women with chronic cough demonstrate an enhanced cough reflex compared with their male counterparts [10]. In terms of health-related quality of life, women are significantly more adversely affected by chronic cough than are men [11].…”
mentioning
confidence: 99%